Development and implementation of a continuing medical education program on non-alcoholic fatty liver disease for primary care practitioners in Europe - Papadakis, Sophia; Anastasaki, Marilena; Gergianaki, Irini; Koek, Ger; Mendive, Juan; Anastasiou, Foteini; Heyens, Leen; Garcia-Retortillo, Montserrat; Muris, Jean; Lionis, Christos (Frontiers in Medicine, 2023)
Background Primary care has a crucial role to play in the prevention, early detection, referral, and risk factor management of non-alcoholic fatty liver disease and non-alcoholic steatohepatitis (NAFLD/NASH). In 2021, a team of European collaborators developed a continuing medical education (CME) program on NAFLD/NASH that consolidates evidence and clinical best practices tailored to the primary care setting. This article reports on the methodology used to design and develop the CME and the results of a feasibility study. Methods An expert advisory group representing both European specialists and general practitioners supported the design of the CME to be implemented in three European settings (Greece, Spain, and Netherlands). The CME features four training modules and problem-based learning using clinical case studies. The CME was tested regarding feasibility and acceptability among a sample of primary care providers (PCPs) in Greece (n = 28) with measurements occurring before, immediately after, and 1 month following the training. Outcome measures included satisfaction with the CME, changes in PCPs’ knowledge, attitudes, confidence, and self-reported clinical practices related to NAFLD/NASH. Results The CME is available as an open-access e-learning course on the European Society for Primary Care Gastroenterology education platform1 in English, Greek, Spanish, and Dutch. The feasibility study documented high levels of satisfaction, with 96% of PCPs reporting they were extremely or very satisfied with the overall training. Statistically significant increases in PCPs’ confidence in NAFLD/NASH-related clinical practices were documented between the pre- and post-assessments. At the follow-up, 62% of GPs reported that the CME had changed their clinical practices related to NAFLD/NASH to a great extent. Conclusion This CME intervention developed by experts and tailored to PCPs in European settings may serve as an asset for increasing knowledge, confidence, and practice behaviors related to NAFLD/NASH.